Pandenomics: Unmasking the Global Recovery Woes - Sthapit, Arhan (Journal of Business and Social Sciences Research, 2021)
The World Bank’s predictions of a strong rebound in the global economy, not seen in the last five decades, are mainly based on the assumption that the mass COVID-19 vaccinations and the government stimulus packages running into trillions of dollars in the rich countries will stimulate growth worldwide. Likewise, it is but natural that even a meagre economic rise this year will post a bigger figure against last year’s poor economic performance hit hard by the pandemic. However, ‘under-managed’ developing countries like Nepal that have neither been able to mass vaccinate their population nor roll out economic stimulus packages are unlikely to share the global growth and reap the growth dividends. Instead, the pandemic is expected to push millions of people into deeper poverty, exacerbated by higher food prices and agricultural commodities worldwide over the last year due to a supply-chain disruption. Adding to these woes, considerable chunks of the population in poor countries like Nepal have been unable to work to eke out a living due to the lockdown imposed to break the chain of infection. The economic recovery woes are most likely to persist.